Editorial: Assessment and National Exams in Social Studies and Social Sciences - Löfström, Jan; Rosenlund, David; Weber, Birgit (JSSE - Journal of Social Science Education, 2023)
In the Introduction are outlined some central questions relating to why there has been increased interest toward assessment, evaluation and testing in educational policy in the last 30 years, and what effect this may have had on pedagogy. In the Introduction attention is drawn to the both negative and positive potential that there is in the new emphasising of student assessment.